Concurrent Overexpression of OsGS1;1 and OsGS2 Genes in Transgenic Rice (Oryza sativa L.): Impact on Tolerance to Abiotic Stresses - James, Donald; Borphukan, Bhabesh; Fartyal, Dhirendra; Ram, Babu; Singh, Jitender; Manna, Mrinalini; Sheri, Vijay; Panditi, Varakumar; Yadav, Renu; Achary, V. Mohan M.; Reddy, Mallireddy K. (Frontiers in Plant Science, 2018)
Glutamine synthetase (GS) is a key enzyme involved in the nitrogen metabolism of higher plants. Abiotic stresses have adverse effects on crop production and pose a serious threat to global food security. GS activity and expression is known to be significantly modulated by various abiotic stresses. However, very few transgenic overexpression studies of GS have studied its impact on abiotic stress tolerance. GS is also the target enzyme of the broad spectrum herbicide Glufosinate (active ingredient: phosphinothricin). In this study, we investigated the effect of concurrent overexpression of the rice cytosolic GS1 (OsGS1;1) and chloroplastic GS2 (OsGS2) genes in transgenic rice on its tolerance to abiotic stresses and the herbicide Glufosinate. Our results demonstrate that the co-overexpression of OsGS1;1 and OsGS2 isoforms in transgenic rice plants enhanced its tolerance to osmotic and salinity stress at the seedling stage. The transgenic lines maintained significantly higher fresh weight, chlorophyll content, and relative water content than wild type (wt) and null segregant (ns) controls, under both osmotic and salinity stress. The OsGS1;1/OsGS2 co-overexpressing transgenic plants accumulated higher levels of proline but showed lower electrolyte leakage and had lower malondialdehyde (MDA) content under the stress treatments. The transgenic lines showed considerably enhanced photosynthetic and agronomic performance under drought and salinity stress imposed during the reproductive stage, as compared to wt and ns control plants. The grain filling rates of the transgenic rice plants under reproductive-stage drought stress (64.6 + 4.7%) and salinity stress (58.2 + 4.5%) were significantly higher than control plants, thereby leading to higher yields under these abiotic stress conditions. Preliminary analysis also revealed that the transgenic lines had improved tolerance to methyl viologen induced photo-oxidative stress. Taken together, our results demonstrate that the concurrent overexpression of OsGS1;1 and OsGS2 isoforms in rice enhanced physiological tolerance and agronomic performance under adverse abiotic stress conditions, apparently acting through multiple mechanistic routes. The transgenic rice plants also showed limited tolerance to the herbicide Glufosinate. The advantages and limitations of glutamine synthetase overexpression in crop plants, along with future strategies to overcome these limitations for utilization in crop improvement have also been discussed briefly.